Antimicrobial Susceptibility and Genomic Analysis of Aliarcobacter cibarius and Aliarcobacter thereius, Two Rarely Detected Aliarcobacter Species - Hänel, Ingrid; Müller, Eva; Santamarina, Belén González; Tomaso, Herbert; Hotzel, Helmut; Busch, Anne (Frontiers in Cellular and Infection Microbiology, 2021)
Arcobacter cibarius and Arcobacter thereius are two rarely detected Arcobacter species. In the study, we analyzed the antimicrobial susceptibility and provide with whole-genome sequencing detailed insights into the genotype and phylogeny. Thermophilic Campylobacter species are the most common bacterial foodborne pathogens causing gastroenteritis in humans worldwide. The genus Arcobacter is part of the Campylobacteraceae family and includes the species Arcobacter butzleri, Arcobacter cryaerophilus, Arcobacter skirrowii, and the rare Arcobacter cibarius and Arcobacter thereius as emergent enteropathogens and potential zoonotic agents. Here, we generated, analyzed and characterized the whole genome sequences of Arcobacter cibarius and Arcobacter thereius that were isolated from water poultry on farms in Germany. Isolates were cultured and identified by MALDI-TOF MS. The identification was verified with PCR. Antibiotic susceptibility testing of isolates was carried out with erythromycin, ciprofloxacin, doxycycline, tetracycline, gentamicin, streptomycin, ampicillin, and cefotaxime using the gradient strip method (E-test). We also sequenced the whole genomes of these isolates and reference strains. Complete genomes for six selected strains are reported. These provide detailed insights into the genotype. With these, we predicted in silico known AMR genes, virulence genes, and plasmid replicons. Phenotypic analysis of resistance showed differences between the prediction of resistance genes and the phenotypic resistance profile. In Arcobacter butzleri, the nucleotide sequence of the gyrA gene (DQ464331) showed a signature mutation resulting in an amino acid change T85>I. Arcobacter cibarius and Arcobacter thereius showed the same gene as assessed by similarity annotation of the mutations 254C>G. The isolates were found to be sensitive to ciprofloxacin. The ciprofloxacin-resistant isolate was associated with the amino acid change T85>I. But this is not predicted with antibiotic resistance databases, before. Ultimately, a phylogenetic analysis was used to determine the genetic relatedness of these isolates and facilitate in future outbreak analysis.